Microperc with Self-Assembled Fr 4.85 Visual Needle and Ureteral Access Sheath - Jiqing Zhang; Ning Kang; Yuguang Jiang; Junhui Zhang (Journal of Investigative Surgery, 2022)
Background Micropercutaneous nephrolithotomy (microperc) is the least invasive among percutaneous nephrolithotripsy (PCNL) procedures. Although microperc has a high stone-free rate and certain advantages over other methods, modifications may be needed to improve the technique. We describe our experience performing microperc using a self-assembled visual needle and ureteral access sheath (UAS). Methods Between June 2016 and April 2019, the data of 30 patients with kidney stones undergoing microperc with our self-assembled 4.8 Fr visual needle combined with a UAS was retrospectively analyzed. Patients were placed in an obilique spine lithotomy position. Results Two cases were excluded: one due to conversion to mini PCNL and the other required flexible ureteroscopy during microperc. The remaining 28 cases included 18 men and 10 women, age 38.4 ± 7.5 years, stone size 1.7 ± 0.4 cm, and stone density on CT 969 ± 233 HU. Operative time was 47 ± 9.9 minutes, visual analogue scale score of tract pain on postoperative day 1 was 2.5 ± 1.0, hemoglobin decrease was 6.4 ± 1.0 g/L, and hospital stay was 3.1 ± 0.8 days. There was 1 case of fever and urinary infection, 2 cases of hematuria, and 1 case of flank pain. All symptoms resolved after conservative or antibiotic treatment. On postoperative day 1, 12 (42.9%) caseswere stone-free. The stone-free rates at postoperative month 1 and 3 were 92.9% (26/28) and 100% (28/28), respectively. Conclusions Our self-assembled visual needle and UAS instrument is effective for microperc. Use of the UAS may improve the operative outcome.